Docência no paradigma inclusivo: a constituição de saberes e práticas no contexto da formação inicial de professores - Ribeiro, Disneylândia Maria (2021)
This thesis presents a research conducted with fourteen students from Pedagogy Course of the Universidade Federal do Ceará whose main goal was to investigate what are the needs teaching knowledge to be built, within the initial training, in order to teach in the inclusive paradigm. More specifically, the study aimed to: reflect on the potentialities and difficulties of initial training in the process of building knowledge related to school inclusion; analyze the politicalpedagogical demands that the school day-to-day presents to initial teacher training, regarding to the construction of inclusive knowledge and practices; identify, in the context of coconstruction with undergraduates, the teaching knowledge potentially favoring an inclusive pedagogical practice; analyze how this knowledge can be built in the context of a collaborative action research. The research was based on the omnilithics perspective of analysis of social and human phenomena and the methodological approach taken is that of collaborative action research, whose contributions consist of the possibility of actively and consciously involving researchers, teachers and students in the research process. The first stage of the research, called co-situation, answered to the need for diagnosis of the problematic under investigation and also constituted the moment of adhesion and incorporation of the participants in the collaborative and formative process, characteristic of this type of investigation. The second stage of the research, referring to cooperation, was characterized by training actions at FACED/UFC with immersion activities in the public schools of Fortaleza, during the first semester in 2019. The third and last phase of the research, called co-evaluation, responded to the need to evaluate the impacts of collaborative action research on the construction of knowledge by the undergraduates involved. Based on these assumptions, the research model adopted in this study brings, as a particular issue: the involvement of subjects in the process of co-construction of practices, in the weaving established between the initial training (undergraduates) and the school, its actors, its demands and its knowledge. The results show that initial training should enable future teachers to build knowledge related to the organization of teaching and pedagogical practices that promote equity in access to the curriculum; the cognitive, affective and social aspects involved in the development and learning of students; the principles and legal provisions guiding the inclusive perspective in education as well as the ethical principles that establish the philosophy of difference at school. The research also points out that initial teacher training processes become more significant when undertaken in a collaborative action research and, in the case of initial training, there is an urgent need for investment in interdisciplinary and cross-cutting activities that enable the confrontation between the educational theories studied in various disciplines with the challenges that arise in schools. In conclusion, it is observed that the educational reality that is configured from the imperative of inclusion requires the training of creative, critical, reflective teachers who value collaborative work and are aware of their role in promoting a more democratic, participatory and inclusive educational system.